Dysplastic follicular dendritic cells in hyaline‐vascular Castleman disease: a rare occurrence creating diagnostic difficulty. Issue 9 (September 2016) - Medina, Edward A.; Fuehrer, Neil E.; Miller, Frank R.; Kinney, Marsha C.; Higgins, Russell A.
Abstract : Follicular dendritic cell (FDC) proliferations and dysplastic FDCs can be seen in Hyaline‐vascular Castleman disease (HVCD). The association between HVCD and FDC sarcoma is well‐documented; dysplastic FDCs may be precursors to FDC sarcoma. Herein, we describe a case of HVCD with strikingly large and dysplastic FDCs, which raised the differential of Hodgkin lymphoma and other neoplasms. Scattered dysplastic FDCs were predominantly in germinal centers and mantle zones, and rarely in interfollicular areas. Although occasional germinal centers contained increased FDCs, no mass forming proliferations were present to suggest FDC sarcoma. Immunostaining demonstrated that the atypical FDCs expressed CD21, clusterin and CXCL13, but not CD23, S100, pankeratin or CD30; they aberrantly expressed epidermal growth factor receptor (EGFR). The present case demonstrates that dysplastic FDCs may be present as isolated cells that require immunophenotyping to distinguish them from malignant entities with similar morphologic features. A variety of FDC markers is required to confirm their origin as the expression of any single marker is not assured, as occurred in this case. Pathologists need be aware of FDC proliferations in HVCD because of their association with FDC sarcoma. Aberrant EGFR expression by dysplastic FDCs may indicate that they are pre‐neoplastic and necessitate long‐term patient follow‐up.